2019
DOI: 10.3390/ijms20194881
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Regulation of Peroxisomal Proteome by Post-Translational Modifications

Abstract: Peroxisomes, which are ubiquitous organelles in all eukaryotes, are highly dynamic organelles that are essential for development and stress responses. Plant peroxisomes are involved in major metabolic pathways, such as fatty acid β-oxidation, photorespiration, ureide and polyamine metabolism, in the biosynthesis of jasmonic, indolacetic, and salicylic acid hormones, as well as in signaling molecules such as reactive oxygen and nitrogen species (ROS/RNS). Peroxisomes are involved in the perception of environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 147 publications
(226 reference statements)
0
39
0
Order By: Relevance
“…In fact, the activation of yeast peroxine Pex11p depends on redox changes in its cysteins (Knoblach & Rachubinski, 2010; Schrader, Bonekamp, & Islinger, 2012). Other PTMs can not be ruled out however, as PEX11a has been identified as a putative target of phosphorylation in Arabidopsis (Kataya, Muench, & Moorhead, 2019; Sandalio et al, 2019). Further proteomic analysis is required to clarify the PTM dependence of PEX11a on the rapid regulation of peroxule formation and the possible involvement of NO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the activation of yeast peroxine Pex11p depends on redox changes in its cysteins (Knoblach & Rachubinski, 2010; Schrader, Bonekamp, & Islinger, 2012). Other PTMs can not be ruled out however, as PEX11a has been identified as a putative target of phosphorylation in Arabidopsis (Kataya, Muench, & Moorhead, 2019; Sandalio et al, 2019). Further proteomic analysis is required to clarify the PTM dependence of PEX11a on the rapid regulation of peroxule formation and the possible involvement of NO.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NO reacts rapidly with reactive oxygen species (ROS) and also regulates ROS production and removal through the protein post‐translational modification of enzymatic sources and antioxidant systems, respectively (Lindermayr & Durner, 2015; Romero‐Puertas & Sandalio, 2016). NO also regulates peroxisomal proteins, antioxidants and ROS‐producing compounds under both normal and stressful conditions caused by heavy metals such as Cd (Gupta & Sandalio, 2012; Ortega‐Galisteo et al, 2012; Sandalio, Gotor, Romero, & Romero‐Puertas, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ethylene biosynthesis is regulated by persulfidation of 1-aminocyclopropane-1-carboxylic acid oxidase (ACO1) in tomato [116]. Recently, a peroxisomal proteome study in Arabidopsis revealed that the interplay of different PTMs such as s-nitrosation, nitration, persulfidation, and acetylation regulates redox signaling to protect proteins against oxidative damage [117]. From an evolutionary point of view, it is reasonable to assume that ancestral purple and green sulfur bacteria lived in an H 2 S-rich atmosphere; and therefore bacteria developed H 2 S-mediated signaling processes to resist oxidative stress.…”
Section: H 2 S Mechanism Of Actionmentioning
confidence: 99%
“…Snitrosylation and therefore, GSNOR, can regulate a large amount of cellular functions and signaling events due to the capacity of alter the activity, stability, conformation, interactions with other molecules or subcellular localization of the S-nitrosated proteins, playing an essential role to protect cells under nitrosative stress (Sevilla et al, 2015a;Romero-Puertas and Sandalio, 2016;Corpas et al, 2019a). Persulfidation H 2 S can exert its function through persulfidation, a PTM affecting the thiol group of cysteine (-SH) in proteins to be modified into a persulfide group (-SSH) (Gotor et al, 2019;Sandalio et al, 2019). H 2 S reacts with either disulfides or sulfenic acids to yield persulfides which are highly reactive to ROS, being oxidized to perthiosulfenic acids (-SSOH), perthiosulfinic (-SSO 2 H), and perthiosulfonic (-SSO 3 H) acids ( Figure 1).…”
Section: S-nitrosationmentioning
confidence: 99%